Development of a mental skills training intervention for the Canadian Special Operations Forces Command: An intervention mapping approach. (September 2020) - Mattie, C. Paige; Guest, Kimberly; Bailey, Suzanne; Collins, Jamie; Gucciardi, Daniel F.
Abstract: Mental skills training (MST) has been well documented in the sport and exercise literature, and there is increasing interest in MST interventions for military populations. Although the considerable research on MST interventions in sport contexts provides a valuable framework from which to develop programming for other high performance contexts, the military, and in particular the Special Operations Force (SOF), represents a unique population for which there is less available evidence for the design and implementation of effective mental performance programming. In this manuscript, we describe the use of Intervention Mapping (IM: Bartholomew Eldridge et al., 2016) in the development and implementation of a customized MST package for the Canadian Special Operations Command. The six stages of the IM protocol were systematically applied to develop the program: 1) needs assessment, including a literature review and focus group consultation; 2) identification of program outcomes and objectives; 3) program design, including the selection of theory-driven and evidence-based methods and practical strategies; 4) program production including pilot testing; 5) planning for adoption, implementation and sustainability, and 6) program evaluation. Although time-consuming, IM is a valuable framework for the development of customized MST for military personnel. This approach offers a logical, methodical approach to integrate relevant theory into program development. Additionally, this process enables ongoing consultation with the end-user, facilitating effective implementation and user acceptance. Finally, because IM involves a highly transparent approach to program development, it enables effective replication of intervention development. Highlights: Application of Intervention Mapping in the development of a customized mental skills training package. Consultation with end-users from project initiation to implementation and evaluation is essential. Matrix linking barriers and facilitators, theoretical mechanisms, intervention functions, and behavior change techniques.